On The Politics of Arabic Literary Translation - MOURAD, Hafida (International Journal of Language and Literary Studies, 2024)
This paper examines the external factors influencing the selection and reception of literary texts in translation, with a focus on the representation of Arab culture in the West. Drawing on Andre Lefevere’s (1992) concept of patronage, the author discusses how patrons, including institutions and individuals, shape the translation and publication of Arabic literary works and explores their impact on the representation of Arab culture in the West. The paper gives examples of several translated Arabic works, reading through the external factors that have influenced their selection, translation, and reception in their target culture. The study contends that the translation of Arabic literature is often driven by ideological and financial motivations, resulting in a restrictive representation of Arab culture that perpetuates stereotypes and exoticism. Furthermore, the paper argues that the “decontextualization” of translated texts leads to a loss of their original identity and purpose, as they are re-inserted within their new context and reinterpreted according to the socio-cultural background of the target audience. By shedding light on the complex dynamics governing literary translation from Arabic, this study highlights the need for understanding the external factors that shape the translation and representation of Arabic literature in the West.